Nuclear and chloroplast DNA phylogeography reveals Pleistocene divergence and subsequent secondary contact of two genetic lineages of the tropical rainforest tree species Shorea leprosula (Dipterocarpaceae) in South‐East Asia. Issue 8 (21st February 2013) - Ohtani, Masato; Kondo, Toshiaki; Tani, Naoki; Ueno, Saneyoshi; Lee, Leong S.; Ng, Kevin K. S.; Muhammad, Norwati; Finkeldey, Reiner; Na'iem, Mohamad; Indrioko, Sapto; Kamiya, Koichi; Harada, Ko; et al.
Abstract Tropical rainforests in South‐East Asia have been affected by climatic fluctuations during past glacial eras. To examine how the accompanying changes in land areas and temperature have affected the genetic properties of rainforest trees in the region, we investigated the phylogeographic patterns of a widespread dipterocarp species, Shorea leprosula. Two types of DNA markers were used: expressed sequence tag‐based simple sequence repeats and chloroplast DNA (cpDNA) sequence variations. Both sets of markers revealed clear genetic differentiation between populations in Borneo and those in the Malay Peninsula and Sumatra (Malay/Sumatra). However, in the south‐western part of Borneo, genetic admixture of the lineages was observed in the two marker types. Coalescent simulation based on cpDNA sequence variation suggested that the two lineages arose 0.28–0.09 million years before present and that following their divergence migration from Malay/Sumatra to Borneo strongly exceeded migration in the opposite direction. We conclude that the genetic structure of S. leprosula was largely formed during the middle Pleistocene and was subsequently modified by eastward migration across the subaerially exposed Sunda Shelf.